The vegetable pathosystem : ecology, disease mechanism, and management - Ansar, Mohammad; Ghatak, Abhijeet (Burlington, ON, Canada ; Palm Bay, Florida : Apple Academic Press, 2020)
"Key Features: Provides an overview of phytopathogens that affect vegetables in various environmental conditions Presents a comprehensive guide to identifying and addressing numerous diseases for individuals in the fields of horticulture Discusses how to manage vegetables affected by specific pathogens Offers eco-friendly approaches to prevent postharvest diseases"--
OCLC-licensed vendor bibliographic record.
Keywords: Vegetables -- Diseases and pests; Plant diseases; SCIENCE / General; SCIENCE / Life Sciences / Botany; TECHNOLOGY / Agriculture / Crop Science